Tinjauan Kriminologi Terhadap Fenomena Filisida (Studi Kasus Pembunuhan Terhadap Anak Oleh Orangtua Tunawisma Di Bekasi) - Mardlatillah, Marhamah Lulu; Koswara, Indra Yudha (Jurnal Ilmiah Wahana Pendidikan, 2026)
The phenomenon of filicide among the homeless is becoming increasingly alarming, as evidenced by a recent case of filicide in the Tambun Bekasi area, where the perpetrator not only killed their child but also exploited them by forcing them to beg. This study aims to analyze the causes and prevention efforts of filicide through a criminological approach, using a case study of child murder by homeless parents in Bekasi. The research method employed is a qualitative approach, involving literature review and descriptive case analysis. The research findings indicate that the filicide committed by homeless parents in Bekasi was influenced by factors such as poverty and economic pressure, where the perpetrator, being homeless, lacked a stable residence and income, thereby driving them to commit filicide. Prevention and mitigation efforts can be carried out through economic empowerment for vulnerable families such as the homeless, through the provision of social assistance, awareness campaigns and anti-violence campaigns against children, as well as skill-training programs for parents among the homeless, thereby helping them to secure income without exploiting their children through begging. Additionally, strict enforcement of the law and rehabilitation for perpetrators are also crucial components in addressing filicide cases. It is hoped that this will minimize filicide cases and protect communities from the negative impacts of economic pressure.